Model Variasi Kalender pada Regresi Runtun Waktu untuk Peramalan Jumlah Pengunjung Grojogan Sewu - Etik Zukhronah; Winita Sulandari; Isnandar Slamet; Sugiyanto Sugiyanto; Irwan Susanto (Universitas Sebelas Maret, 2021)
Abstract. Grojogan Sewu visitors experience a significant increase during school holidays, year-end holidays, and also Eid al-Fitr holidays. The determination of Eid Al-Fitr uses the Hijriyah calendar so that the occurrence of Eid al-Fitr will progress 10 days when viewed from the Gregorian calendar, this causes calendar variations. The objective of this paper is to apply a calendar variation model based on time series regression and SARIMA models for forecasting the number of visitors in Grojogan Sewu. The data are Grojogan Sewu visitors from January 2009 until December 2019. The results show that time series regression with calendar variation yields a better forecast compared to the SARIMA model. It can be seen from the value of root mean square error (RMSE) out-sample of time series regression with calendar variation is less than of SARIMA model.Keywords: Calendar variation, time series regression, SARIMA, Grojogan Sewu